The Economy of Communist China, 1949-1969 - Cheng, Chu-yuan (Michigan Monographs In Chinese Studies, 2020)
Economic development in mainland China during the first two decades of Communist control provides a typical example for the difficult task to transform a vast underdeveloped agrarian economy into a modern industrial one. In the first half of this period, a series of massive transformations of social and economic institutions was accompanied by a drafted industrialization program; the result was an impressive speed-up in economic growth. The second decade witnessed an economic crisis (1960-62) and a political upheaval (1966-68). These disruptions marred the economic performance over the period as a whole. Consequently, the long-term growth rate appears to have been only moderate. The Economy of Communist China reviews selected aspects of the economy. After examining the development strategy, it analyzes the quantitative trends and the structural changes. The book goes on to analyze the key factors contributing to the earlier growth and the elements responsible for the later disruption and finally assesses the impact of the Cultural Revolution on the Chinese economy and the prospects of the current Third Five-Year Plan. The text includes a bibliography of selected materials on Chinese economic development.